Basic Teaching Skills of Microteaching for Graduate Students’ Competencies as Prospective Teacher: What Should They Consider? - Nur Fitria, Tira (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This study describes basic teaching skills in microteaching to enhance graduate students’ competencies as prospective teachers through a library research approach. The finding shows that basic skills for microteaching are skills to open and close learning, skills of explanation, asking/questioning skills, skills in using variations, skills to provide reinforcement, small group and individual teaching skills, class management skills, and skills in guiding small group discussions. Microteaching is a teaching practice model conducted on a limited scale to develop essential teaching skills. The limitations include specific competencies, subject matter, time, number of students, and targeted skills. Typically lasting 10–40 minutes with 1–10 students, microteaching consists of three main stages: Preparation, Implementation, and Feedback. In the Preparation Stage, teachers design a learning activity plan according to the allotted time, organize student numbers, prepare teaching materials, and arrange instructional media. During the Implementation Stage, prospective teachers deliver content clearly, use appropriate language, manage the classroom effectively, provide exercises, and evaluate learning outcomes. The Feedback Stage involves receiving input from observers or peers through discussion or Q&A, helping participants identify areas for improvement. Microteaching trains fundamental teaching skills such as opening and closing lessons, explaining concepts, questioning techniques, using variations, giving reinforcement, managing classrooms, teaching individuals and small groups, and guiding discussions.